Policy Recommendations Based on National-Level Material Flow Analysis: Comparative Study of Iran and Three Selected Countries - Javad Mashayekh; Seyed Hossein Nekoomanesh Fard; Maryam Bahrami Kahyash Nejad (بهبود مدیریت, 2018)
Economic development and increasing wealth in the last century has resulted in a sevenfold growth in the per-capita raw material consumption, culminating in a global average of more than 10 tons in 2010. Environmental hazards and the threat of resource scarcity had been the driving force behind a multitude of researches on the consumption indicators and the flow analysis of materials. The export and import flow of materials to Iran is of strategic importance, since, on the one hand, the Iran's economy relies heavily on the export of raw materials, and, on the other hand, imports of some critical materials are subject to restrictions due to international sanctions. However, despite the strategic importance of the topic, neither a comprehensive national-level study on the material consumption patterns nor a comparison with other economies has been carried out. This paper aims to introduce several material flow indicators and briefly compare Iran, Brazil, India and Turkey from material consumption viewpoint. Investigating such indicators shows that beside Iran's considerable dependency on the exportation of raw materials, the country is importing significant amount of processed materials with high hidden flow input in the form of finished goods. Furthermore, this study demonstrates that in addition to the fact that the per-capita material footprint of Iran is nearly 50% higher than the global average, there is a still increasing trend, which necessitates the policymakers to devise better policies to optimize this trend.